The Ivory Coast, an economic power in West Africa (strength analysis) - (:unkn) unknown (My University, 2024)
West Africa has a certain number of emerging countries in 2022, despite the Covid 19 pandemic, which has greatly reduced the economic growth of certain countries, and also the health situation, some countries have as well managed to recover their economic growth to rise among the developing countries. These include the richest countries in West Africa : Nigeria, Ghana, and Ivory Coast.Indeed, Côte d'Ivoire is an economic power in the region thanks to several criteria, and which are the result of the development of its economic and financial policy over the past decades, and also the development of its much more sectoral policy. targeted with effective results.This work seeks to determine the bases of these economic powers in West Africa, taking the case of Côte d'Ivoire, of which it consists of presenting on the one hand, the current economic situation in West Africa, and on the other hand, study the economic power model for the case of Côte d'Ivoire.
Keywords: African Research